(untitled) (Journal of Institute of Science and Technology, 2019)
One of the major objectives of keeping the wild animals in captivity is their successful breeding, population growth and future translocation. However, many species have lesser behavioral flexibility and fail to establish a viable population in captive conditions due to poor management, intolerant climatic conditions, competitions with other co-housed species, diseases, etc. Blackbuck (Antilope cervicapra) is a nationally endangered and protected mammalian species of Nepal. Blackbucks have been kept under captivity of Mrigasthali enclosure at Pashupatinath Temple area in Kathmandu since 2004 AD and the population has dwindled sharply in recent years. This study was designed to assess the population trend and diurnal activity pattern of the species in the Mrigasthali enclosure. Population census data for the last fifteen years were analyzed and behavioral samplings were done by ‘Focal animal sampling’ and ‘Scan sampling’ methods from 5th April to 29th July 2016. The study revealed a sharp decrease of the population since the outbreak of the foot-and-mouth disease in 2014 exposing the remnant population into the risk of extirpation. The surviving individuals have the diurnal activity pattern and the time budgets prominently different than that of the wild populations, especially, they invest lesser time on feeding and more time on resting. Living in open areas despite cooler climate, intense competition for food and space with spotted deer and monkeys, lower behavioral flexibility of the species, anthropogenic disturbances, stochasticity related to the smaller population size, etc. were perceived as the major threats to the Blackbuck in Mrigasthali enclosure.